On some new generalized difference sequence spaces defined by a sequence of moduli - Atici, Gulcan; Bektas, Cigdem A. (Versita, 2011)
In this paper, we define the new generalized difference sequence spaces [V, lambda, F, p, q](0)(Delta (v) (m) ), [V, lambda, F, p, q](1)(Delta (v) (m) ) and [V, lambda, F, p, q](a)(Delta (v) (m) ). We also study some inclusion relations between these spaces. (C) 2011 Mathematical Institute Slovak Academy of Sciences
Keywords: difference sequence spaces; sequence of Moduli; seminorm